Lactic acid bacteria bacteriocins as novel antimicrobials against antibiotic-resistant Streptococcus pneumoniae in opthalamic infections - Marriam Wasif; Nazish Mazhar Ali; Syed Abdullah Mazhar; Sher Muhammad Zaman; Seher kiran; Maham Chaudhry; Ibtissem Louiz; Amor Hedfi; Manel Ben Ali; Arslan Muhammad Ali Khan; Itrat Zahra (Molecular Biology Reports, 2026)

Genome-wide study uncovering the role of GPAT gene family in watermelon and functional validation of ClGPAT8 against cold stress - Ali Aslam; Xiaomeng Wang; Muhammad Waseem; Muhammad Azam; Ashir Masroor; Qinghua Shi; Sher Muhammad; Aseel Smerat; Muhammad Khuram Razzaq; Ruimin Zhang (Plant Science, 2026)

Reversible -NH2/-NH3+ switching drives proton-coupled electron transfer for selective CO2-to-CO photoreduction in S-scheme MOF/g-C3N4 heterojunction - Sharafat Ali; Sher Ali; Ahmed Ismail; Yong Wang; Syed Ul Hasnain Bakhtiar; Qaisar Alam; Pir Muhammad Ismail; Wajid Ali; Ahmad Iqbal; Polycarpos Falaras; Jiabao Yi; Fazal Raziq; et al. (Chemical Engineering Journal, 2026)

Lactiplantibacillus plantarum AS21 Reduces Colitis in Mice by Modulating Inflammation, Gut Barrier Function, and Microbiota in an Intervention Dose and Time-dependent Manner - Ali Sher Bacha; Mengyan Chen; Zitong Ding; Mengya Jia; Hu Chen; Ikram Khan; Muhammad Ishaq; Azmat Ullah Jan; Ashiq Khan; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Bifidobacterium animalis subsp. lactis and Enterococcus hirae Enhance Immunity by Modulating Gut Microbiota and Metabolic Pathways in Immunosuppressed Mice - Azmat Ullah Jan; Hu Chen; Muhammad Ishaq; Mengya Jia; Ali Sher Bacha; Qiang Li; Mengyan Chen; Zitong Ding; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Erratum to: Bifidobacterium animalis subsp. lactis and Enterococcus hirae Enhance Immunity by Modulating Gut Microbiota and Metabolic Pathways in Immunosuppressed Mice - Azmat Ullah Jan; Hu Chen; Muhammad Ishaq; Mengya Jia; Ali Sher Bacha; Qiang Li; Mengyan Chen; Zitong Ding; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Tailoring strontium-nickel supported reduced graphene oxide nanostructure for synergistic catalytic hydrogen generation from sodium borohydride and photodegradation of organic pollutant - Rana Nauman Hassan; Faryal Ali; Shoaib Akhtar; Abu Bakar Siddique; Khaled Fahmy Fawy; Muhammad Sher; Muhammad Ashraf Shaheen; Muhammad Fayyaz ur Rehman; Umar Nishan; Tauqeer Ahmad; Arshad Ali; Azhar Abbas (Fuel, 2026)

Climate driven drought risk and machine learning approaches for urban resilience and sustainable water governance - Shan-e-hyder Soomro; Huaibin Wei; Muhammad Waseem Boota; Nishan-E-Hyder Soomro; Sher Ali; Sana Nazli; Caihong Hu; Jiali Guo (Environmental Research, 2026)

Host–Microbiota Metabolic Interactions in Atherosclerosis: Oral, gut, and Blood Perspectives - Ikram Khan; Muhammad Irfan; Ali Sher Bacha; Imran Khan; Yasir Ali; Zhiqiang Li (Probiotics and Antimicrobial Proteins, 2026)

Pangenome-assisted characterization of TaBAM genes and association of TaBAM16-1B with NDVI in wheat - Maira Anam; Zulqurnain Khan; Muhammad Ali Sher; Muhammad Sajjad; Muhammad Kashif Naeem; Zijin Zhang; Sania Javeed; Fatima Javeria; Jing Chen; Shoaib Ur Rehman (Theoretical and Applied Genetics, 2026)

Deep learning-based classification of nitrate and nitrite concentrations from water samples using colorimetric test strip images - Muhammad Roman; Mazhar Sher; Chamika Kuruppuarachchi; Arshid Ali; Chulwoo Pack; Azlan Zahid; Ali Mirzakhani Nafchi (Environmental Monitoring and Assessment, 2026)
Accurate monitoring of nitrate and nitrite concentrations in water is essential for sustainable agriculture, safeguarding public health, and protecting aquatic ecosystems from nutrient pollution. Traditional methods for detecting nitrate and nitrite in water samples are precise but costly, complex, and time-consuming, limiting their practicality for frequent on-site testing. This research proposes deep learning-based computer vision techniques to classify nitrate and nitrite concentrations using images of colorimetric test strips. An RGB IMX219 camera was used to acquire images of colorimetric test strips under standardized, controlled illumination conditions to ensure consistent image quality. A total of 1938 nitrate images and 1190 nitrite images were collected before augmentation. After preprocessing and training-only data augmentation, both classical machine learning baselines based on hand-crafted color and texture features and deep learning models—including a multilayer perceptron (MLP) and convolutional neural networks (AlexNet, VGG16, ResNet18, and GoogLeNet)—were trained and evaluated using an independent test set and stratified fivefold cross-validation. For nitrate classification, ResNet18 and GoogLeNet achieved near-perfect 100% test accuracy, with mean cross-validation accuracy of 99.97% ± 0.04%, substantially outperforming classical baseline models based on hand-crafted color and texture features, which achieved at most 83.5% test accuracy. For nitrite classification, GoogLeNet achieved the strongest overall performance, with a test accuracy of 97.48% and a fivefold cross-validation accuracy of 95.22% ± 1.17%, substantially outperforming the best classical baseline model, which achieved a maximum test accuracy of 83.19%. These results demonstrate that deep CNN-based feature learning provides a significant performance advantage over simpler methods under controlled imaging conditions, supporting the suitability of the proposed system for rapid, image-based water quality assessment and motivating future evaluation under broader real-world deployment scenarios.

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Development of an AI-Enabled Vision-Based On-Site Rapid Detection of Nitrates and Nitrites from Drainage Samples - Muhammad Roman; Azlan Zahid; Ali Mirzakhani Nafchi; Mazhar Sher (Water, Air, & Soil Pollution, 2026)
Plant growth is significantly impacted by the concentration of nutrients in the soil. Accurate and real-time measurement of nitrates and nitrites levels remains a significant challenge. Existing laboratory-based methods are expensive, time-consuming, and labor-intensive, highlighting the need for a rapid, on-site solution. This study proposes a rapid method for measuring nitrates and nitrite levels in water samples collected from tile drainage. We utilized Hach Nitrate and Nitrite test strips for image dataset collection as these test strips change color based on the concentration of nitrate and nitrite in the water samples. A purpose-built black box, equipped with an internal lighting arrangement for imaging test strips, was designed to collect images of the test strips. Unlike many existing smartphone-based colorimetric approaches, which are sensitive to ambient lighting variations and often rely on external calibration or offline analysis, the proposed system integrates a controlled illumination environment with real-time edge computation for robust on-site detection of nitrate and nitrite. An Nvidia Orin Nano module, connected with an IMX219 camera sensor, was used to capture images of the test strips. Image preprocessing was performed, followed by the implementation of a VGG16-based network for feature extraction. A dataset of approximately 3128 images spanning multiple nitrate and nitrite concentration levels was collected under controlled imaging conditions. Multiple machine learning models including logistic regression (LR), support vector machines (SVM), k-nearest neighbors (KNN), naïve Bayes (NB), and random forest (RF) were evaluated for classification. The nitrate detection using KNN achieved an accuracy of 99.96% training, 99.92% testing, and 99.79% cross-validation. For nitrite detection, the SVM model achieved accuracy of 99.02%, 98.04%, and 98.07% for training, testing, and cross-validation, respectively, demonstrating both systems' high reliability and practical applicability for real-time monitoring. The total system cost is approximately USD 300, highlighting the affordability and practicality of the proposed solution for on-site water quality monitoring. This technology can enable farmers, water quality researchers, and agronomists to efficiently monitor the levels of nitrates and nitrites in tile drainage samples, enabling data-driven decisions to maximize crop yields.

Retraction Note: Morphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Developing a RUSLE-Based Tool for Analyzing Climate Induced Soil Erosion and Reservoir Sedimentation in the Tarbela Region - Muhammad Arif Goheer; Sher Shah Hassan; Syeda Rosheen Raza Kazmi; Muhammad Taimoor Ashfaq Malik; Syed Zee Ali Shan (International Journal of Environmental Research, 2026)

Electron-rich sulfur sites and dual interfacial bonds in S-scheme heterojunction enable high quantum yield and stable hydrogen production - Sharafat Ali; Sajjad Ali; Shu-Long Li; Ahmed Ismail; Sher Ali; Pir Muhammad Ismail; Syed Ul Hasnain Bakhtiar; Fazal Raziq; Mohammad Z. Rahman; Liang Qiao (Chemical Engineering Journal, 2026)

Genetic and morphological data indicate the occurrence of a Rhipicephalus sp. and the absence of Rhipicephalus linnaei in Pakistan - Muhammad Numan; Zaibullah Khan; Sher Bahadar Khan; Mohibullah Shah; Iram Liaqat; Itabajara da Silva Vaz Junior; Lidia Chitimia-Dobler; Abid Ali; Zhihua Sun; Mashal M. Almutairi (Tropical Animal Health and Production, 2026)

The potential influence of food additives and contaminants on the gut microbiota: A comprehensive review - Sana Ullah; Sher Ali; Muhammad Atif; Muhib Ullah; Ghulam Nabi; Lucas Gabriel Dionisio Freire; Eliana Setsuko Kamimura; Amir Sasan Mozaffari Nejad; Carlos Augusto Fernandes de Oliveira (Food and Chemical Toxicology, 2025)

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

Structure-guided drug repurposing and dynamics simulation reveal anti-viral candidates for Bourbon virus - Israr Hussain; Itazaz Ul Haq; Muhammad Rahiyab; Junaid Khan; Rooh Ullah; Syed Shujait Ali; Hassan Sher; Arshad Iqbal (In Silico Pharmacology, 2025)

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

An overview of ethnobotanical investigations for primary healthcare: a case study from Mardan district, Pakistan - Muhammad Mohsin; Musheerul Hassan; Ivana Vitasović-Kosić; Mona S. Alwahibi; Sher Wali; Qoryog’diyev Zufar Oxunjonovich; Muhammad Abdul Aziz; M. Ajmal Ali; Rainer W. Bussmann; Arshad Mehmood Abbasi (Plant Biosystems, 2025)

Mapping mangroves land suitability using machine learning and MCDM in the Indus Delta, Pakistan - Sher Shah Hassan; Muhammad Ajmal; Muhammad Arif Goheer; Zainab Ali; Muhammad Suleman (Theoretical and Applied Climatology, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Occurrence of aflatoxins and effect of preventive practices to inhibit fungal growth and aflatoxin production in leftover flat bread/chapati used as animal feed and stored in Pakistani dairy farms - Mavra Amin; Amir Ismail; Iqra Naeem; Usama Nasir; Muhammad Riaz; Yun Yun Gong; Sher Ali; Michael N. Routledge; Amna Iqbal; Asifa Saif; Carlos Augusto Fernandes Oliveira (Journal of Stored Products Research, 2025)

Association mapping of leaf rust disease resistance and yield related traits in bread wheat using a high density 90K SNP array - Muhammad Rauf Shah; Muhammad Ali Sher; Salma Bashir; Muhammad Zeshan Zafer; Douglas Law; Sania Begum; Nasr Ullah Khan; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Daniel K. Y. Tan; Muhammad Yasin (Journal of Plant Diseases and Protection, 2025)

RETRACTED ARTICLE: ArticleNoteMorphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Heavy metals pollution in riverine sediments: Distribution, source, and environmental implications - Kifayatullah Khan; Muhammad Younas; Muhammad Yaseen; Hassan Sher; Afsheen Maryam; Sobhy M. Ibrahim; Adnan Adnan; Ahmad Ali; Muhammad Fawad; Akhtar Zeb Khan; Nasrullah Khan; Izaz Ali Shah (Environmental Monitoring and Assessment, 2025)

Novel mutations in exon 2 of follistatin (FST) gene associated with wool fiber diameter in sheep - Tahira Mir; Muhammad Ibrahim; Muhammad Siraj; Sajid Ali Khan Bangash; Sher Hayat Khan; Majid Khan; Muhammad Tayyab; Sohail Ahmad (Small Ruminant Research, 2025)

Harmonizing traditional and biotechnological approaches to engineer crop microbiomes: Enhancing resilience optimization - Muhammad Siddique Afridi; Abdul salam; Sher Ali; Sumaira; Willian César Terra; Baber Ali; Muhammad Atif Muneer; Gustavo Santoyo (Biocatalysis and Agricultural Biotechnology, 2024)

An SNP based genotyping assay for genes associated with drought tolerance in bread wheat - Abdul Rauf; Muhammad Ali Sher; Umar Farooq; Awais Rasheed; Muhammad Sajjad; Ruilian Jing; Zulqurnain Khan; KOTB A. Attia; Arif Ahmed Mohammed; Sajid Fiaz; Jing Chen; Shoaib Ur Rehman (Molecular Biology Reports, 2024)

Greenly synthesized zinc oxide nanoparticles: An efficient, cost-effective catalyst for dehydrogenation of formic acid and with improved antioxidant and phyto-toxic properties - Sami Ullah; Muhammad Shaban; Abu Bakar Siddique; Anam Zulfiqar; Naveed Shahzad Lali; Muhammad Naeem-ul-Hassan; Muhammad Imran Irfan; Muhammad Sher; Muhammad Fayyaz ur Rehman; Ali Hanbashi; Fahad Y. Sabei; Hatem M.A. Amin; et al. (Journal of Environmental Chemical Engineering, 2024)

From lake to fisheries: Interactive effect of climate and landuse changes hit on lake fish catch? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Majid Rasta; Caihong Hu; Chengshuai Liu; Yinghai Li; Ao li; Jijun Chen; Chunyun Zhu; Sher Ali; Jiali Guo; et al. (Environmental Research, 2024)

Efficacy of activated carbon using Salvadora persica stem for remediation of potentially toxic dyes from aqueous solution - Muhammad Bilal; Wahid Ullah; Tahir Abbas; Javed Ali; Syed Shah Hassan; Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan (Environmental Monitoring and Assessment, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Population exposure to emerging perfluoroalkyl acids (PFAAs) via drinking water resources: Application of multivariate statistics and risk assessment models - Kifayatullah Khan; Muhammad Younas; Jafar Ali; Noor Samad Shah; Yasar N. Kavil; Mohammed A. Assiri; Xianghui Cao; Hassan Sher; Afsheen Maryam; Yunqiao Zhou; Muhammad Yaseen; Li Xu (Marine Pollution Bulletin, 2024)

Silver oxide doped iron oxide/alginate nanocomposite coated cotton cloth for selective catalytic reduction of potassium ferricyanide - Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan; Abdullah M. Asiri; Tahseen Kamal; Muhammad Bilal; Shahid Ali Khan (Chemosphere, 2024)

The therapeutic effect of BODIPY-based photosensitizers against acetylcholinesterase for the treatment of Alzheimer’s disease - Mushtaq Ahmed; Nadia Mushtaq; Naila Sher; Rahmat Ali Khan; Muhammad Amir Masood (Journal of Proteins and Proteomics, 2024)

Improved bio-oil yield from thermo-catalytic pyrolysis of Citrus limetta waste over pumice: Determination of kinetic parameters using Kissinger method - Faisal Muhammad; Jan Nisar; Ghulam Ali; Farooq Anwar; Syed Tasleem Hussain; Sher Wali Khan (Bioresource Technology Reports, 2023)

Balanced NPK Nutrition Improves Forage Productivity and Quality of Pearl Millet Grown in Semi-arid Regions of Pakistan - Ahmad Sher; Zahid Ali Akbar; Abdul Sattar; Sami Ul-Allah; Muhammad Ijaz; Roberta Calone; Lorenzo Barbanti (Journal of Soil Science and Plant Nutrition, 2023)

A decline in snow cover area of Passu and Ghulkin valleys between 1995 and 2022 - Imran Hussain; Mumtaz Ali; Sher Muhammad; Wajid Hassan; Salar Ali; Zakir Hussain; Syed Hammad Ali; Shaukat Ali; Muhammad Younis Khan (Journal of Mountain Science, 2023)

Improving Nitrogen Acquisition and Utilization Through Root Architecture Remodelling: Insight from Legumes - Muhammad Nadeem; Muhammad Yahya; Jingyang Tong; Liaqut Shah; Sana Ullah Khan; Ahmad Ali; Alam Sher; Najeeb Ullah; Abdul Waheed (Journal of Plant Growth Regulation, 2023)
In crop species, nutrient deficiency severely damages plant growth and developmental processes, leading to end-yield penalties. Root architecture remodelling is considered a key factor underpinning nutrient-poor soil environments. Adequate nitrogen (N) supply can play a significant role in sustaining crop productivity on nutrient-deficient soils. However, excessive application of nitrogenous fertilizer may pollute the soil and increase the production cost for the growers. To tackle this problem, crop breeders have made tremendous efforts to improve the N-use efficiency of agricultural crops. This article summarizes the recent progress in identifying QTLs/genes, regulatory pathways, and hormonal crosstalk involved in the growth and development of legumes roots system. Moreover, we have described the progress in microbe–root symbiosis via QTLs/genes regulations, which results in improved N acquisition. Understanding the molecular mechanisms that regulate the root architecture in response to N availability may help to strengthen the root system of legumes and promote environmental friendly and sustainable agriculture.

Modelling the impact of climate change on dengue outbreaks and future spatiotemporal shift in Pakistan - Alia Saeed; Shaukat Ali; Firdos Khan; Sher Muhammad; Michelle Simões Reboita; Abdul Wali Khan; Muhammad Arif Goheer; Mumtaz Ali Khan; Ramesh Kumar; Aamer Ikram; Aliya Jabeen; Sathirakorn Pongpanich (Environmental Geochemistry and Health, 2023)

Efficient Regeneration in Sugarcane Using Thin Cell Layer (TCL) Culture System - Aneela Iqbal; Raham Sher Khan; Mubarak Ali Khan; Karim Gul; Muhammad Aizaz; Muhammad Usman; Muhammad Arif (Sugar Tech, 2023)

Occurrence and Distribution of Heavy Metals in Mining Degraded Soil and Medicinal Plants: A Case Study of Pb/Zn Sulfide Terrain Northern Areas, Pakistan - Javed Nawab; Muhammad Idress; Sajid Ullah; Gul Rukh; Rimsha Zainab; Hassan Sher; Junaid Ghani; Sardar Khan; Zahid Ullah; Imran Ahmad; Syed Weqas Ali (Bulletin of Environmental Contamination and Toxicology, 2023)

Wavelet coherence of monsoon and large‐scale climate variabilities with precipitation in Pakistan - Azfar Hussain; Jianhua Cao; Shaukat Ali; Waheed Ullah; Sher Muhammad; Ishtiaq Hussain; Haider Abbas; Kalpana Hamal; Shankar Sharma; Mobeen Akhtar; Xiuqin Wu; Jinxing Zhou (International Journal of Climatology, 2022)
Monsoon and its teleconnection with earth system internal processes affect the spatiotemporal distribution of precipitation and water resources . In this paper, the wavelet coherence analysis has been utilized, a time and frequency domain methodology for comparing the spectral features of two independent time series superior to linear approaches. This technique is used to capture the significant modes of variabilities in the Indian Summer Monsoon Index (ISMI) and large‐scale climate indices (CIs) between ocean–atmosphere oscillations, like Indian Ocean Dipole (IOD), El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), Southern Oscillation Index (SOI), North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), and Arctic Oscillation (AO) over Pakistan. Precipitation time series during 1960–2016 revealed significant interannual coherences with ISMI, whereas the remaining CIs (IOD, ENSO, PDO, SOI, NAO, AMO, and AO) revealed interannual, decadal and interdecadal coherences. However, AO revealed strongest coherences in R‐II, III, and VI at interdecadal scales among all CIs. Overall, the interannual cycles on ISMI are 2.8 years, IOD 1–5.3 years, PDO 0–5.3 years, SOI 1–5.3 years, NAO 0–5 years, AO 0–5 years, and AMO 0–8.3 years. Whereas, the remaining CIs shared interdecadal coherences over particular regions. The ISMI displayed coherences (except in the UIB) with the large‐scale CIs over various homogenous regions on an interannual scale. The dominant influence of ISMI is observed in R‐II and III; the significant coherences in R‐II ranged from ~8 to 32 months (~0.8–2.8 years). The IOD and NAO have major coherences than the remaining large‐scale CIs ranging from ~16 to 64 months (1.3–5.3 years). The AO has the most significant coherences observed in R‐II, III, and VI on the decadal/interdecadal scale from 128 months and above (almost 10–15 years). On a 1.0‐year timescale, all homogenous regions demonstrated strong intermittent coherence with ISMI, IOD, ENSO, PDO, SOI, NAO, AMO, and AO. These findings have substantial implications for decision‐makers and scientists in Pakistan looking to enhance water resource planning and operations in the face of future climate uncertainties.

Observed trends and variability of seasonal and annual precipitation in Pakistan during 1960–2016 - Azfar Hussain; Jianhua Cao; Shaukat Ali; Sher Muhammad; Waheed Ullah; Ishtiaq Hussain; Mobeen Akhtar; Xiuqin Wu; Yinghui Guan; Jinxing Zhou (International Journal of Climatology, 2022)
Long‐term precipitation monitoring plays a vital role in water resource management and disaster prevention and mitigation. This study assesses spatial and temporal trends in seasonal and annual precipitation in Pakistan between 1960 and 2016 at an interannual scale. The Mann–Kendall (MK) test, Sen's slope (SS) estimator, and Sequential Mann–Kendall (SQMK) test were employed to assess trends. Cluster analysis and L ‐moment approach were used to identify the homogenous precipitation regions. In general, increasing precipitation trends between 1960 and 2016 were evident. Results indicated increasing precipitation in winter, autumn, summer and annual scale at the rates of 0.20, 2.18, 5.16, and 10.89 mm·decade −1 , respectively. In spring, the precipitation trend shows a decreasing trend at −0.67 mm·decade −1 . Moreover, a significant decreasing trend occurred in winter in southern Pakistan. The overall increasing trends were more noticeable between 1960 and 1988, compared to the declining precipitation during 1989–2016. SQMK analysis indicates a clear downward trend in most regions during 1989–2016, except in autumn. Annual precipitation has increased topographically except at 500 m and 1,500 m during 1960–2016 with a significant increase of 1.37 mm·decade −1 at elevation

Contrasting treeline dynamics of pine and birch in response to climate warming in the Karakoram - Munawar Ali; Shalik Ram Sigdel; Xiangyu Zheng; Fayaz Asad; Ru Huang; Haifeng Zhu; Sher Muhammad; Iqtidar Hussain; Saulat Hussain; J. Julio Camarero; Eryuan Liang (Trees, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Linking Plants Functioning to Adaptive Responses Under Heat Stress Conditions: A Mechanistic Review - Mahmood Ul Hassan; Tassaduq Rasool; Chandni Iqbal; Adnan Arshad; Muhammad Abrar; Muhammad Mohsin Abrar; Muhammad Habib-ur-Rahman; Mehmood Ali Noor; Alam Sher; Shah Fahad (Journal of Plant Growth Regulation, 2022)

Exogenous application of strigolactone alleviates drought stress in maize seedlings by regulating the physiological and antioxidants defense mechanisms - Abdul Sattar; Sami Ul-Allah; Muhammad Ijaz; Ahmad Sher; Madiha Butt; Tahira Abbas; Muhammad Irfan; Tehreem Fatima; Saleh Alfarraj; Sulaiman Ali Alharbi (Cereal Research Communications, 2022)

Wetting mechanism and morphological adaptation; leaf rolling enhancing atmospheric water acquisition in wheat crop—a review - Zulfiqar Ali; Sabah Merrium; Muhammad Habib-ur-Rahman; Sadia Hakeem; Muhammad Abu Bakar Saddique; Muhammad Ali Sher (Environmental Science and Pollution Research, 2022)
Several plant species such as grasses are dominant in many habitats including arid and semi-arid areas. These species survive in these regions by developing exclusive structures, which helps in the collection of atmospheric water. Before the collected water evaporates, these structures have unique canopy structure for water transportation that plays an equivalent share in the fog-harvesting mechanism. In this review, the atmospheric gaseous water harvesting mechanisms and their affinity of measurements were discussed. Morphological adaptations and their role in the capturing of atmospheric gaseous water of various species were also discussed. The key factor for the water collection and its conduction in the wheat plant is the information of contact angle hysteresis. In wheat, leaf rolling and its association with wetting property help the plant in water retention. Morphological adaptations, i.e., leaf erectness, grooves, and prickle hairs, also help in the collection and acquisition of water droplets by stem flows in directional guide toward the base of the plant and allow its rapid uptake. Morphological adaptation strengthens the harvesting mechanism by preventing the loss of water through shattering. Thus, wheat canopy architecture can be modified to harvest the atmospheric water and directional movement of water towards the root zone for self-irrigation. Moreover, these morphological adaptations are also linked with drought avoidance and corresponding physiological processes to resist water stress. The combination of these traits together with water use efficiency in wheat contributes to a highly efficient atmospheric water harvesting system that enables the wheat plants to reduce the cost of production. It also increases the yielding potential of the crop in arid and semi-arid environments. Further investigating the ecophysiology and molecular pathways of these morphological adaptations in wheat may have significant applications in varying climatic scenarios.

Bio-diesel production of sunflower through sulphur management in a semi-arid subtropical environment - Athar Mahmood; Masood Iqbal Awan; Sana Sadaf; Ahmed Mukhtar; Xiukang Wang; Sajid Fiaz; Sher Aslam Khan; Habib Ali; Faran Muhammad; Zafar Hayat; Farhana Gul; Shah Fahad (Environmental Science and Pollution Research, 2022)

Tree-ring-based temperature reconstruction from the western Himalayan region in northern Pakistan since 1705 C.E. - Adam Khan; Moinuddin Ahmed; Narayan Prasad Gaire; Javed Iqbal; Muhammad Faheem Siddiqui; Afsheen Khan; Mohib Shah; Ali Hazrat; Najm Us Saqib; Wali Khan Mashwani; Sher Shah; Sanjaya Bhandari (Arabian Journal of Geosciences, 2021)

Variability and Predictability of Summer Monsoon Rainfall over Pakistan - Muhammad Adnan; Firdos Khan; Nadia Rehman; Shaukat Ali; Sher Shah Hassan; Muhammad Mubashar Dogar; Shahbaz Mehmood; Shabehul Hasson (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Performance evaluation of participatory irrigation management as an alternative to a state‐managed irrigation system* - Sabir Hussain; Mudasser Muneer Khan; Muhammad Shoaib; Ali Raza; Syyed Adnan Raheel Shah; Tanveer Ahmed Khan; Sher Khan (Irrigation and Drainage, 2021)
The Lower Bari Doab Canal (LBDC) system is one of the large old irrigation systems in Punjab, Pakistan. To overcome problems of water distribution and management in conventional state‐managed irrigation, a participatory irrigation management (PIM) system was introduced in the LBDC command area in 2012. From the very large system of the LBDC, 20 different kinds of distributaries were selected in this study as representatives for evaluating performance of the new system. The primary data were gathered through questionnaires and by interviewing farmers, whereas the secondary data were gathered from the related offices of the Punjab Irrigation Department. The analysis of collected data illustrates that water service deliveries (WSDs) were poor even after implementation of PIM. The research shows that under administration of both systems, efficiency regarding provision of water seemed to be poor. The outcomes show that with the passage of time, recovery ( abiana ) decreased after implementation of the PIM system but the financial sustainability of PIM has improved compared to state administration. Finally, the current study recommends institutional reforms in PIM and comprehensive work on educating the farmers about their role in PIM as a mandatory component for improving efficiency of the PIM system.

Future climatic changes, extreme events, related uncertainties, and policy recommendations in the Hindu Kush sub-regions of Pakistan - Shaukat Ali; Alia Saeed; Rida Sehar Kiani; Sher Muhammad; Firdos Khan; Romaisa Babar; Asif Khan; Muhammad Shahid Iqbal; Muhammad Arif Goheer; Wajid Naseem; Shah Fahad (Theoretical and Applied Climatology, 2021)

Interactive Effect of Biochar and Silicon on Improving Morpho-Physiological and Biochemical Attributes of Maize by Reducing Drought Hazards - Abdul Sattar; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Madiha Butt; Muhammad Irfan; Muhammad Shahid Rizwan; Hakoomat Ali; Mumtaz A. Cheema (Journal of Soil Science and Plant Nutrition, 2020)

Heterologous expression of azoreductase-encoding gene azrS of Bacillus sp. MR-1/2 for enhanced azo dye decolorization and wastewater treatment - Ali Abbas; Aqsa Mushtaq; Ayesha Iftikhar Cheema; Faisal Mahmood; Muhammad Asaf Khan; Tahir Naqqash; Mohsin Khurshid; Irfan Manzoor; Sher Muhammad; Muhammad Shahid (Archives of Microbiology, 2020)

Heat treatment effects on chilling injury and disease incidence in sweet orange fruits stored at chilling and non-chilling temperatures - Ijaz Hussain; Abdur Rab; Naqib Ullah Khan; Zarina Bibi; Shah Masaud Khan; Naushad Ali; Muhammad Saeed; Sher Aslam Khan; Sardar Ali; Ghulam Dastagir; Muhammad Sajid (Journal of Consumer Protection and Food Safety, 2019)

Physiological and biochemical attributes of bread wheat (Triticum aestivum L.) seedlings are influenced by foliar application of silicon and selenium under water deficit - Abdul Sattar; Mumtaz Akhtar Cheema; Ahmad Sher; Muhammad Ijaz; Sami Ul-Allah; Ahmad Nawaz; Tahira Abbas; Qasim Ali (Acta Physiologiae Plantarum, 2019)

Input Selection of Wavelet-Coupled Neural Network Models for Rainfall-Runoff Modelling - Muhammad Shoaib; Asaad Y. Shamseldin; Sher Khan; Muhammad Sultan; Fiaz Ahmad; Tahir Sultan; Zakir Hussain Dahri; Irfan Ali (Water Resources Management, 2019)

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability - Regie Lyn P. Santos-Cortez; Valeed Khan; Falak Sher Khan; Zaib-un-Nisa Mughal; Imen Chakchouk; Kwanghyuk Lee; Memoona Rasheed; Rifat Hamza; Anushree Acharya; Ehsan Ullah; Muhammad Arif Nadeem Saqib; Izoduwa Abbe; et al. (Human Genetics, 2018)

Biodegradation of plastics: current scenario and future prospects for environmental safety - Temoor Ahmed; Muhammad Shahid; Farrukh Azeem; Ijaz Rasul; Asad Ali Shah; Muhammad Noman; Amir Hameed; Natasha Manzoor; Irfan Manzoor; Sher Muhammad (Environmental Science and Pollution Research, 2018)

Potentially Toxic Metals and Biological Contamination in Drinking Water Sources in Chromite Mining-Impacted Areas of Pakistan: A Comparative Study - Javed Nawab; Sardar Khan; Muhammad Amjad Khan; Hassan Sher; Ubaid Ur Rehamn; Sharafat Ali; Syed Mehboob Shah (Exposure and Health, 2017)

Using Landsat images to monitor changes in the snow-covered area of selected glaciers in northern Pakistan - Chaman Gul; Shi-chang Kang; Badar Ghauri; Mateeul Haq; Sher Muhammad; Shaukat Ali (Journal of Mountain Science, 2017)

Comparative Assessment of Synthetic-derived and Conventional Bread Wheat Advanced Lines Under Osmotic Stress and Implications for Molecular Analysis - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Awais Rasheed; Hassan Sher; Alvina Gul Kazi; Abdul Mujeeb-Kazi (Plant Molecular Biology Reporter, 2015)

Exploitation of synthetic-derived wheats through osmotic stress responses for drought tolerance improvement - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Manzoor Ahmad; Hassan Sher; Sammer Fatima; Alvina Gul Kazi; Awais Rasheed; Abdul Mujeeb-Kazi (Acta Physiologiae Plantarum, 2014)